شعرية المكان في الشعر الشعبي " شعراء وادي سوف أنموذجا - زغدي، تيسير, غريبي، نور الإيمان (جامعة الوادي University of Eloued, 2019)
إن الشعر الشعبي يتنوع حسب الطبوع الفنية والأذواق ويعبر بصدق عن إحساس ذاكرة جماعية، كما أنه فعل ثقافي مستمر يعالج القضايا الإجتماعية والسياسية والثقافية، ولقد نال المكان حظه في الشعر الشعبي فشكل عند هؤلاء الشعراء مرتكزا للإبداع الشعري حيث لم يكن لديهم مجرد صورة أو شكل هندسي، وإنما هو أحد العناصر التي يشتغل عليها العمل الأدبي ليصبح ذا بعد رمزي يعكس مفهوما جماليا، ويمكن القول أن الفضاء المكاني الفني يرتبط بالخيال والحالة النفسية وتفاعل الشاعر، فيمتزج خيال الشاعر بالمكان لينتج مكان فنيا مشيعا بالجمال. The popular poetry is varied according to artistic idioms and tastes and expresses truthfully from a sense of collective memory. It is also an ongoing cultural act that deals with social, political and cultural issues. The place gained its popularity in popular poetry. These poets formed a basis for poetic creativity, But it is one of the elements that work on the literary work to become a symbolic dimension reflects an aesthetic concept, and can be said that spatial space of art is linked to the imagination and psychological state and the interaction of the poet, combining the poet's imagination of the place to produce a place of art and beauty.
Keywords: الشعرية، المكان، الشعر الشعبي; poetry, place, popular poetry